From training to workflow: a mixed-methods assessment of integration of Doppler into maternity ward triage and admission in Tanzania - Mary Carol Jennings; Dunstan R. Bishanga; Sheena Currie; Barbara Rawlins; Gaudiosa Tibaijuka; Ahmad Makuwani; Jim Ricca; John George; Filbert Mpogoro; Stella Abwao; Lusekelo Njonge; Jeremie Zougrana; et al. (Journal of Global Health Reports)
# Background